Lid Analysis using EPA SWMM 5.2 Application (Case Study: DPR Road Section, Padang City) - Silta Yulan Nifen; Afdal Saputra; Angelalia Roza (CIVED, 2025)
Padang City has experienced rapid development in infrastructure, but the limited green open space presents a significant challenge to the city's drainage system, resulting in frequent flooding during the rainy season which has a negative impact on the economy, health, and safety of the community. This study aims to identify the intensity of rainfall, analyze the implementation of Low-Impact Development (LID) technology and without LID implementation using EPA SWMM 5.2 software in the DPR Street area, Dadok Tunggul Hitam Village, Padang City. The practical implications of the implementation of Low Impact Development (LID) for general city management are to reduce drainage loads by managing rainfall locally, improve water quality by reducing rainfall pollution, reduce flood risks by managing rainfall effectively, improve city aesthetics by creating green and beautiful open spaces, and reduce infrastructure costs by managing rainfall locally and reducing the need for large drainage systems. The main benefits of the research results for flood management policies in Padang City are to improve the quality of life of city residents by creating a healthier and more comfortable environment, increase city resilience to climate change and natural disasters, and improve resource management efficiency by managing rainfall locally. Using 10 years of rainfall data from BMKG and primary data related to drainage channel dimensions, hydrological and hydraulic analyses and drainage system simulations were carried out. The results of the study showed that the application of LID, such as Rainfall Garden, Rainfall Barrel, Bioretention Cell, Infiltration Trench, and Permeable Pavement, application of LID an area can reduce the depth of inundation by 57,717%, the volume of runoff by 74.247%, and the peak runoff by 68,069%. The implementation of LID in an area of ​​73.54 Ha has proven effective in reducing the risk of flooding, strengthening drainage infrastructure, and providing sustainable solutions in dealing with urbanization in Padang City.